Modular 3D-Printed Peg Biofilm Device for Flexible Setup of Surface-Related Biofilm Studies - Zaborskytė, Greta; Wistrand-Yuen, Erik; Hjort, Karin; Andersson, Dan I.; Sandegren, Linus (Frontiers in Cellular and Infection Microbiology, 2022)
Medical device-related biofilms are a major cause of hospital-acquired infections, especially chronic infections. Numerous diverse models to study surface-associated biofilms have been developed, however, their usability varies. Often, a simple method is desired but without sacrificing throughput and biological relevance. Here we present an in-house developed 3D printed device (FlexiPeg) for biofilm growth, conceptually similar to the Calgary Biofilm device but aimed at increasing ease of use and versatility. Our device is modular with the lid and pegs as separate units, enabling flexible assembly with up- or down-scaling depending on the aims of the study. It also allows easy handling of individual pegs, especially when disruption of biofilm populations is needed for downstream analysis. The pegs can be printed in, or coated with, different materials to create surfaces relevant to the study of interest. We experimentally validated the use of the device by exploring the biofilms formed by clinical strains of Escherichia coli and Klebsiella pneumoniae, commonly associated with device-related infections. The biofilms were characterized by viable cell counts, biomass staining and SEM imaging. We evaluated the effects of different additive manufacturing technologies, 3D printing resins and coatings with, for example, silicone, to mimic a medical device surface. The biofilms formed on our custom-made pegs could be clearly distinguished based on species or strain across all performed assays, and they corresponded well with observations made in other models and clinical setting, for example, on urinary catheters. Overall, our biofilm device is a robust, easy to use and relevant assay, suitable for a wide range of applications in surface-associated biofilm studies, including materials testing, screening for biofilm formation capacity and antibiotic susceptibility testing.